OP0148 MEPOLIZUMAB FOR EOSINOPHILIC GRANULOMATOSIS WITH POLYANGIITIS (EGPA): A RETROSPECTIVE REAL-WORLD EUROPEAN STUDY ON 142 PATIENTS. (2nd June 2020) - Bettiol, A.; Urban, M. L.; Alberici, F.; Agostini, C.; Baldini, C.; Bozzolo, E.; Cameli, P.; Crimi, N.; Del Giacco, S.; Egan, A.; Espigol-Frigole, G.; Felicetti, M.; et al.
Abstract : Background: Evidence on the efficacy of Mepolizumab (MEPO) in Eosinophilic Granulomatosis with Polyangiitis (EGPA) is scarce [1]. Objectives: To assess the efficacy and safety of MEPO in real-life clinical practice. Methods: We retrospectively included patients diagnosed with EGPA and treated with MEPO (100 or 300 mg/month). MEPO efficacy was evaluated in the first 12 months in terms of systemic disease and asthma control. The occurrence of any adverse event (AE) was recorded. Results: 142 patients were included (38% males; median age 46.4 (IQR 36.7-54.4); 110 and 32 on MEPO 100 and 300 mg/month, respectively). General, ear-nose-throat, pulmonary, and neurological symptoms significantly decreased during treatment (table 1 ). MEPO accounted for a significant reduction in the BVAS (figure 1 ) and for a steroid sparing effect (figure 2 ). The proportion of patients with asthma attacks decreased by 90% at 12 months compared to t0, and asthma-related emergency accesses dropped from 17.4% to 2.3%. Overall, 21.1% of patients had a non-serious AE. Conclusion: MEPO effectively controlled systemic and respiratory EGPA symptoms in a large European cohort, with no major safety concerns. References: [1]Wechsler et al. MEPO or Placebo for Eosinophilic Granulomatosis with Polyangiitis. NEJM. 2017 Disclosure of Interests: Alessandra Bettiol: None declared, Maria Letizia Urban: None declared, Federico Alberici: None declared, Carlo Agostini: None declared, Chiara Baldini: None declared, Enrica Bozzolo: None declared, Paolo Cameli: None declared, Nunzio Crimi: None declared, Stefano Del Giacco: None declared, Allyson Egan: None declared, Georgina Espigol-Frigole Consultant of: Roche and Janssen, Mara Felicetti: None declared, Marco Folci: None declared, Paolo Fraticelli: None declared, Marcello Govoni: None declared, Anna Kernder Grant/research support from: Grant/research support from: GlaxoSmithKline and UCB Pharma for performing the LuLa-study., Carlo Lombardi: None declared, Giuseppe Lopalco: None declared, Claudio Lunardi: None declared, Aladdin J Mohammad Speakers bureau: lecture fees from Roche and Elli Lilly Sweden, PI (GiACTA study), Frank Moosig: None declared, Simone Negrini: None declared, Thomas Neumann: None declared, Pavel Novikov Grant/research support from: This work was supported by the 5-100 Project, Sechenov University, Moscow, Giuseppe Paolazzi: None declared, paola parronchi: None declared, Luca Quartuccio Consultant of: Abbvie, Bristol, Speakers bureau: Abbvie, Pfizer, Vito Racanelli: None declared, Carlo Salvarani: None declared, Maxime Samson: None declared, Jan Schroeder: None declared, Savino Sciascia: None declared, Renato A. Sinico: None declared, Benjamin Terrier: None declared, Paola Toniati: None declared, Domenico Prisco: None declared, Augusto Vaglio: None declared, Giacomo Emmi: None declared